Boldness in Male and Female Zebrafish (Danio rerio) Is Dependent on Strain and Test - Mustafa, Arshi; Roman, Erika; Winberg, Svante (Frontiers in Behavioral Neuroscience, 2019)
Differences in selection pressure in nature and labs have profound effects on zebrafish strains. The widely used AB strain of zebrafish has been domesticated over several decades. Recently, there has been an upsurge in the availability of genetically modified lines, e.g., the spiegeldanio (spd), which has a mutation in the fibroblast growth factor receptor 1a (fgfr1a) gene. This mutant strain (fgfr1a) has previously been reported to be bolder than fish of the Tübingen strain, from which it was generated. Our knowledge on behavioral differences between different zebrafish strains, relative to wild-caught zebrafish, is limited. In the present study we compare behaviors related to interpretation of boldness in male and female offspring (F1) of wild-caught fish, AB and fgfr1a−/− zebrafish. A second aim of the study was to compare the behavior of fish from these strains when tested in different behavioral assays, i.e., shelter seeking, novel tank diving and scototaxis tests. The results demonstrate that behavioral variation exists both within and between the strains, but interpretation of boldness reveals a complex pattern in which behavior differs between strains but is also related to sex and test. Therefore, a careful assessment of various strains of fish using both males and females is warranted in order to strengthen interpretation of results. This is especially important in studies where zebrafish are used as model organisms for human conditions as well as studies evaluating the effects of pharmacological or toxicological substances on behavior.